Strengthening National Values and Economic Independence of Students through Integrated Education at Pondok Pesantren - Sudawan Supriadi; Ridwan Santoso; Sri Wahyuni; Agustin Wela Sasih (KURAS Institute, 2025)
This study aims to examine the role of integrated education that combines formal education, diniyah (religious) teaching, and entrepreneurship training in Islamic boarding schools to strengthen the national values and economic independence of students. This study uses a Mixed Methods Sequential Exploratory design involving three key informants and forty respondents at Pondok Pesantren Al Muhajirin, Kabupaten Batanghari Jambi. Qualitative data were obtained from interviews, while quantitative data were collected using questionnaires and analyzed through Multivariate Analysis of Covariance tests. The results showed that Integrated Education has a significant role in the variables of national values ​​and economic independence of students. This is evidenced by the analysis output obtained on national values ​​with an F value = 17.0 and a p value < .001 and economic independence with an F value = 24.3, and a p value < .001. Post hoc tests found that the integrated education implementation model was significantly superior in increasing economic independence compared to the national values ​​variable. In short, the synergy of these three aspects of integrated education effectively cultivates graduates with strong national character and economic competitiveness. Islamic boarding schools and policymakers are encouraged to adopt a holistic framework that serves as a systematic solution for producing graduates who are religiously committed, nationalistically inclined, and financially competitive.